DFT study on the adsorption of deprotonated benzotriazole on the defective copper surfaces. (1st July 2021) - Li, Fengting; Wang, Zhikun; Jiang, Yunying; Li, Chunling; Sun, Shuangqing; Chen, Shougang; Hu, Songqing
Highlights: The adsorption of BTA on three defects and ideal surface was studied by using density functional theory. The energy and active site of three types of copper defect surfaces were analysed. The atom charge, charge density difference and partial density of states were analysed. The relationship between defect types and BTA adsorption was clarified. Abstract: Density functional theory calculation was conducted to investigate the adsorption behavior and mechanism of benzotriazole (BTA) on the copper surface with the defects of vacancy, impurity, and grain boundary (GB). On the Cu (111) surface with vacancies, BTA tends to obliquely, rather than vertically, adsorb on the copper surface. The surface doped with Zn and O has stronger adsorption activity for negatively charged particles compared with the surface doped with Ni and S. For impurity and GB surface, the adsorption energy and transferred charge show that the oblique and horizontal adsorption configurations are more stable than the vertical adsorption of BTA. Our findings provide profound explanation for corrosion inhibitor protection of defective metal surface.